Is Life all Vanity? A Thematic Analysis of the Book of Ecclesiastes - Mercado, Giovani (12th International Scholars Conference 2025, 2026)
This paper sought to understand the meaning of life according to author of the book of Ecclesiastes, who had experienced every pleasure he had desired, yet had declared life as “vanity.” Answers were also sought as to what satisfies man, and how everyone ought to live. To arrive at these answers, a qualitative content analysis was done on the 12 chapters of the Book of Ecclesiastes in the New King James Version, comprising a total of 222 verses. Thematic analysis was done, generating 58 descriptive codes and six themes through manual coding. The themes of the futility of human pursuits and the inevitability of death and shared fate shed light on the meaning of life amidst the apparent meaninglessness. Enjoying the fruit of one’s labor and companionship, coupled with the rigors of everyday work, were themes that satisfy the human soul. Themes on how to live wisely and peaceably with God and among other people were also generated. Lastly, the theme of fearing God and obeying his commandments defined the meaning and purpose of life for all men. These findings downplay atheistic claims that, on the surface, seem to agree with the Ecclesiastes narrative. Based on the experiences of someone with great wisdom, finding the meaning of life is finding its purpose, which, if deeply appreciated, will increase life satisfaction, increase connectedness with others, and reduce depression, especially in the young.